An Iconographic Study of Sultan Mohammad Naqash's Painting Called "Masti Lahouti - Nasuti " - Seyed Mohammad Taheri Qomi (IJCAS (International Journal of Creative and Arts Studies), 2022)
The painting called “Lahouti (divine) and Nassotti (worldly) Intoxication”, has been drawn on a page in Divan Hafez by Sam Mirza, whose painter was Sultan Mohammad Naqash, a Tabriz Safavid School painter, who is regarded as one of the shining examples of pictorial icons for the creation of a mystical, symbolic, and theatrical atmosphere as well as visual attractions. The present study is a theoretical one and has been conducted through a descriptive-analytical method, analyzing the iconography used in the above-mentioned painting by collecting images and information using the library method. By utilizing a historical and semantic approach to Hafiz's poetry as well as the artistic style of Sultan Mohammad, this study aims at decrypting the mystical and narrative concepts in this painting. The main research question raised here is: "What are the philosophical, mystical, lyrical and mythological concepts behind the relationship between icons and the visual atmosphere dominating the image?" Review of literature was conducted on Hafez's life as well as semantics and stylistics used in his odes as well as the history of the Turkmen and Tabriz Safavid Painting Schools and the style of Sultan Mohammad Naqash, recorded in articles and books by Iranian and foreign authors. The above-mentioned resources were studied, and it was concluded that Sultan Mohammad’s exaggerated, and humorous style matches Hafiz's quick-witted outlook and it is appropriate to divide the painting into three distinctive parts from top to bottom and consider the appropriate icons for each of the sections through a mystical and separating perspective as Nassott, Malakut and Lahout. Kajian Ikonografi Lukisan Sultan Muhammad Naqash Berjudul "Masti Lahouti - Nasuti" Abstrak Lukisan yang berjudul “Lahouti (divine) and Nassotti (worldly) Intoxication”, digambar pada sebuah halaman di Divan Hafez oleh Sam Mirza, di mana pelukisnya adalah Sultan Mohammad Naqash, seorang pelukis Sekolah Tabriz Safawi, yang dianggap sebagai salah satu contoh cemerlang ikon bergambar untuk penciptaan suasana mistis, simbolis dan teatrikal serta atraksi visual. Penelitian ini bersifat teoretis dan dilakukan melalui metode deskriptif-analitik, menganalisis ikonografi yang digunakan dalam lukisan tersebut dengan mengumpulkan gambar dan informasi menggunakan metode kepustakaan. Dengan memanfaatkan pendekatan historis dan semantik pada puisi-puisi Hafez serta gaya artistik Sultan Mohammad, kajian ini bertujuan untuk mendekripsi konsep mistik dan naratif pada lukisan. Pertanyaan penelitian utama yang diangkat yaitu: "Apa konsep filosofis, mistis, liris, dan mitologis dibalik hubungan antara ikon dan suasana visual yang mendominasi gambar?" Tinjauan literatur dilakukan pada kehidupan Hafez serta semantik dan gaya yang digunakan dalam syairnya serta sejarah Sekolah Lukisan Safawi Turkmenistan dan Tabriz dan gaya Sultan Mohammad Naqash, yang dicatat dalam artikel dan buku oleh penulis Iran dan asing. Melalui sumber yang didapat maka disimpulkan bahwa gaya Sultan Mohammad yang berlebihan dan humoris cocok dengan pandangan Hafez yang cerdas dan pantas untuk membagi lukisan menjadi tiga bagian yang berbeda dari atas ke bawah dan mempertimbangkan ikon yang sesuai untuk masing-masing bagian melalui perspektif mistis dan terpisah sebagai Nassott, Malakut dan Lahout.